Are we achieving or missing the objectives of fasting? - Omer, Spahic (www.islamicity.org, 2019)
As yet another blessed month of Ramadan unfolds, the perennial, and somewhat disturbing, truth re-emerges. That truth is that a great many Muslims fast. In many countries, overwhelming majorities – perhaps all -- do so. In some countries, it is an anomaly to see or discover that any Muslim, from any societal stratum, does not fast, even for legitimate reasons. Heavy penalties are imposed on those who openly violate the sanctity of Ramadan and fasting. It is illegal in most Muslim counties to drink or eat in public during Ramadan. A person -- sometimes even a non-Muslim -- can be sent to jail, heavily fined, or may yet be beaten by vigilantes. However, the overall situation of Muslims as the best and standard-setting ummah (community), and the supposed history and civilization makers, does not improve. Yet, one gets a feeling that it is getting worse by the day, despite the apparent prevalent faithfulness and virtue which, by the letter and spirit of revelation, guarantees prosperity and happiness. At the collective level, Muslims are losing respect in the eyes of most of the world, so much so that it seems that there is hardly anyone who genuinely respects them, or takes them seriously. It is as if Muslims do not do enough with reference to the proposition of changing what is in themselves and their hearts, so that Almighty Allah could take care of and change their condition as a community. Why is it so when the primary objective of Ramadan and fasting is the increase in piety, God-fearing and God-consciousness (taqwa), intended to inspire a person to be on guard against wrong and immoral actions and keen to do things that please Almighty Allah alone? Why is it so when fasting, as a revolutionary experience, is designed to make us better and more enlightened people, closer to Allah and each other? Why is it so, furthermore, when fasting and everything that goes with it, such as collective prayers, sharing meals, brotherhood, universal kindness and benevolence, as well as outpouring philanthropy, are as much personal experiences as co-operative engagements and missions?